Teleost fish models in membrane transport research: the PEPT1(SLC15A1) H+–oligopeptide transporter as a case study. (19th September 2013) - Romano, Alessandro; Barca, Amilcare; Storelli, Carlo; Verri, Tiziano
Abstract Human genes for passive, ion‐coupled transporters and exchangers are included in the so‐called solute carrier (SLC) gene series, to date consisting of 52 families and 398 genes. Teleost fish genes for SLC proteins have also been described in the last two decades, and catalogued in preliminary SLC‐like form in 50 families and at least 338 genes after systematic GenBank database mining (December 2010–March 2011). When the kinetic properties of the expressed proteins are studied in detail, teleost fish SLC transporters always reveal extraordinary 'molecular diversity' with respect to the mammalian counterparts, which reflects peculiar adaptation of the protein to the physiology of the species and/or to the environment where the species lives. In the case of the H+–oligopeptide transporter PEPT1(SLC15A1), comparative analysis of diverse teleost fish orthologs has shown that the protein may exhibit very eccentric properties in terms of pH dependence (e.g. the adaptation of zebrafish PEPT1 to alkaline pH), temperature dependence (e.g. the adaptation of icefish PEPT1 to sub‐zero temperatures) and/or substrate specificity (e.g. the species‐specificity of PEPT1 for the uptake of l‐lysine‐containing peptides). The revelation of such peculiarities is providing new contributions to the discussion on PEPT1 in both basic (e.g. molecular structure–function analyses) and applied research (e.g. optimizing diets to enhance growth of commercially valuable fish).